2020
DOI: 10.1111/hae.13975
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mosaicism in haemophilia: A practical review to help evaluate the risk of transmitting the disease

Abstract: Approximately 70% of patients with haemophilia exhibit a clear inheritance pattern, while for the remaining 30%, patients are the first to be diagnosed in their family and are considered sporadic cases. In such a setting, the determination of carrier status and the risk estimation of disease transmission to another child are major challenges for genetic counselling. Large studies have suggested that genetic testing reveals 70% of sporadic patients' mothers are carriers. In the remaining 30%, in some apparently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…The significant proportion of sporadic cases (47%) agrees with that reported in Argentinian families (53%), and among the Inv22 positive families, 50% were sporadic (De Brasi et al, 2000; Mårtensson et al, 2016). The significant proportion of de novo pathogenic variants (3/23 of SHA positive to F8 inversions, 13%) along with the negative result in the probands' mothers recalls the probability of mosaicism reported in the literature (Kasper & Lin, 2007; Lannoy & Hermans, 2020). (Kasper & Lin, 2007).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The significant proportion of sporadic cases (47%) agrees with that reported in Argentinian families (53%), and among the Inv22 positive families, 50% were sporadic (De Brasi et al, 2000; Mårtensson et al, 2016). The significant proportion of de novo pathogenic variants (3/23 of SHA positive to F8 inversions, 13%) along with the negative result in the probands' mothers recalls the probability of mosaicism reported in the literature (Kasper & Lin, 2007; Lannoy & Hermans, 2020). (Kasper & Lin, 2007).…”
Section: Discussionsupporting
confidence: 53%
“…We present the diagnosis of 40 carriers and 73 noncarrier cases for Mårtensson et al, 2016). The significant proportion of de novo pathogenic variants (3/23 of SHA positive to F8 inversions, 13%) along with the negative result in the probands' mothers recalls the probability of mosaicism reported in the literature (Kasper & Lin, 2007;Lannoy & Hermans, 2020). (Kasper & Lin, 2007).…”
Section: Detection Of F8 Inth22 and F8 Inth1 Inversions In Sha Patimentioning
confidence: 85%
“…As indicated in Figure 3, an apparently STR result showed that one paternal allele and one maternal allele were found at all loci. Considering that the mosaicisms proportion of our case was close to 50% in both amniotic uid cells and umbilical cord blood, the mechanism of BRTM in our case was plausible due to a de novo mitotic error may originate in a zygote within the rst or early cell divisions, which results in a mosaic embryo with the variant present in a half proportion of cells, and this mosaicism can affect somatic and/or gonadal tissues 20 .However, due to the growth deviation of different cell types in the process of cells culture, the mosaic ratio of different fetal tissues may be different.…”
Section: Discussionmentioning
confidence: 65%
“…Measurement of FVIII from cord blood of male babies with mothers who carry the hemophilia gene is recommended immediately after birth. In this case there are no risks for the baby (5,39). A timetable illustration of when genetic testing can take place is found in Figure 2.…”
Section: Figurementioning
confidence: 99%
“…In approximately 30% of sporadic cases (i.e., no known family history of hemophilia), the variant (mutation) causing the disease cannot be found in the mother. However, with the conventional Sanger sequencing, carriership cannot be conclusively ruled out since she may be a mosaic not detected by this technique (39).…”
Section: Figurementioning
confidence: 99%